سوق أهراس ONA التكنولوجيات الحديثة كمدخل لتحسين ادارة الموارد البشرية في المؤسسات الاقتصادية دراسة حالة الديوان الوطني للتطهير - - نسيبة جواد; سارة بوزيد (My University, 2022)
This study aims to highlight the relationship between modern technologies and human resource management in the economic institutions sector, through a theoretical treatment of concepts related to the topic studied, with the projection of this on the National Office for Disinfection, Souk Ahras Branch, relying on a form directed to the employer of the institution, where It was distributed to a sample of 30 employer, and the results were analyzed using the SPSS statistical package. The study reached many results, perhaps the most important of which are: Proving the validity of the hypotheses put forward, which is the existence of an impact of modern technologies as an independent variable with its three dimensions on human resource management, which represents the dependent variable in this study, and the impact of information and communication technology on human resource management in general is considered. Direct and indirect impact, as it was found that the provision of modern technology in human resource management contributes to increasing the efficiency of the employee and the administrative process in the organization ......................................................... تهدف هذه الدراسة إلى إبراز العلاقة الرابطة بين التكنولوجيات الحديثة وإدارة الموارد البشرية، بقطاع المؤسسات الاقتصادية، وذلك من خلال المعالجة النظرية للمفاهيم المتعلقة بالموضوع المدروس، مع إسقاط ذلك على مؤسسة الديوان الوطني للتطهير فرع سوق أهراس، معتمدين في ذلك على استمارة موجهة لعمال المؤسسة، حيث تم توزيعها على عينة في 30 عامل، وتحليل النتائج باستخدام برنامج الحزم الإحصائية . وقد توصلت الدراسة إلى العديد من النتنائج ، إثبنات الفرضنيات المطروحنة، والمتمثلنة في وجود أثر للتكنولوجيات الحديثة كمتغير مستقل بأبعادها الثلاثة على إدارة الموارد البشرية و التي تمثل المتغير التابع في هذه الدراسة، تنأثير تكنولوجينا المعلومات والاتصال على إدارة الموارد البشرية بصفة عامة، تأثير، كما تم التوصل إلى أن توفير وسنائل التكنولوجيا الحديثة في إدارة الموارد البشرية يساهم في زيادة كفاة الموظف والعملية الإدارية في المؤسسة.